Counteraction corruption under martial law: an analysis of problems and opportunities (Law and Safety, 2024)
The article is devoted to the analysis of problems and possibilities of counteracting corruption in the conditions of martial law. The beginning of the full-scale invasion of russia led not only to significant financial problems in Ukraine, but also to an increase in the level of corruption, which led to active actions by the state to counteract it. State bodies that regulate corruption manifestations are considered, as well as the normative and legal framework for combating corruption in the conditions of martial law in Ukraine is analyzed, with the determination of opportunities in this area.It was noted that the most striking manifestations of corruption are the transfer of funds (undeclared) to other accounts (money laundering through virtual accounts), embezzlement of humanitarian aid, enrichment with financial funds received in the form of aid during the conflict, non-payment of taxes due to martial law, etc. It has been determined that the tax burden, regulatory pressure, monopolization, an imperfect judicial system, and directly corruption are the causes of the shadow economy.The steps taken by state bodies and the programs introduced by them to reduce the level of corruption are analyzed. The latest indicators of the level of corruption in Ukraine were considered, it was noted that the indicators of the level of combating corruption in the conditions of martial law increased significantly (compared to last year), which became possible thanks to the effective activity of the bodies created to fight corruption and other state institutions.Quantitative indicators of high-profile suspicions and convictions for 2023 were considered, while taking into account the confiscation of russian property, which was transferred to a special fund of the budget of Ukraine. It was determined that aspects of public procurement and access to open data about officials, enterprises, etc. remain problematic.Recommendations aimed at combating corruption in the country have been proposed, among which the key ones are: 1) institutional recommendations providing for the introduction of reform of the Accounting Chamber and the State Audit Service of Ukraine; 2) legal recommendations that provide for the development of effective control mechanisms by public organizations, effective use of assets of corrupt officials and their accomplices for the needs of the state; 3) structural recommendations providing for the formation of specialized departments (and the appointment of responsible persons) with the aim of preventing and detecting corruption and other similar situations.